Efforts to Realize The Profile of Pancasila Students based on the Local Culture of the Tengger Tribe in SD di Atas Awan Jarak Ijo, Malang Regency - Selly Anggraita; Raden Bambang Sumarsono; Sunarni Sunarni; Juharyanto Juharyanto (Universitas Negeri Malang, 2026)
Efforts to realize Pancasila Student Profiles based on the local culture of the Tengger tribe are a process of realizing students with character based on the values and culture that develop in a tribe. This study aimed to explain the phenomena that occur at SD di Atas Awan Jarak Ijo to realize the Pancasila Student Profile based on the local culture of the Tengger tribe. This study uses a qualitative approach with a type of research design through case studies. Data collection techniques were carried out through interviews, observations, and documentary studies with snowball sampling. The research showed that SD di Atas Awan Jarak Ijo Malang Regency embodies the Pancasila Student Profile based on the local cultural values of the Tengger tribe by adopting the local culture of the Tengger tribe, namely Kasada, and Karo. The school adopted Kasada and Karo’s activities with a permit/dispensation strategy and went home early. Efforts to realize the Pancasila Student Profile are supported by internal driving factors, namely domicile teachers, culturally strong school members, and student awareness, and there are also external driving factors, namely support from parents, society, and technological developments. However, there are also internal inhibiting factors, namely students playing on mobile phones, and facilities, while external inhibiting factors, namely globalization, community environment, and per capita income.